2018
DOI: 10.3390/ijms19102911
|View full text |Cite
|
Sign up to set email alerts
|

The Risk G Allele of the Single-Nucleotide Polymorphism rs928413 Creates a CREB1-Binding Site That Activates IL33 Promoter in Lung Epithelial Cells

Abstract: Cytokine interleukin 33 (IL-33) is constitutively expressed by epithelial barrier cells, and promotes the development of humoral immune responses. Along with other proinflammatory mediators released by the epithelium of airways and lungs, it plays an important role in a number of respiratory pathologies. In particular, IL-33 significantly contributes to pathogenesis of allergy and asthma; genetic variations in the IL33 locus are associated with increased susceptibility to asthma. Large-scale genome-wide associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…This eQTL signal A also comprised an SNP (rs928413, in LD r 2 5 0.96 with rs992969) where the phenotype-risk allele was recently found to form a CREB1 binding site, functionally activating the IL33 promotor in lung epithelial cells. 41 This allele associates with higher level of eosinophils, higher risk of (eosinophilic) asthma, and increased IL33 expression in brushes in our cohorts. As lung tissue resection samples mainly consist of parenchymal lung tissue with minor contributions of airway epithelial cells, while bronchial brushes contain more than 90% bronchial epithelial cells, 48 we interpret these data as evidence for regulation of IL33 expression in bronchial epithelium.…”
Section: Functional Effects Of Phenotype-associated Il33 Polymorphismmentioning
confidence: 59%
See 1 more Smart Citation
“…This eQTL signal A also comprised an SNP (rs928413, in LD r 2 5 0.96 with rs992969) where the phenotype-risk allele was recently found to form a CREB1 binding site, functionally activating the IL33 promotor in lung epithelial cells. 41 This allele associates with higher level of eosinophils, higher risk of (eosinophilic) asthma, and increased IL33 expression in brushes in our cohorts. As lung tissue resection samples mainly consist of parenchymal lung tissue with minor contributions of airway epithelial cells, while bronchial brushes contain more than 90% bronchial epithelial cells, 48 we interpret these data as evidence for regulation of IL33 expression in bronchial epithelium.…”
Section: Functional Effects Of Phenotype-associated Il33 Polymorphismmentioning
confidence: 59%
“…To investigate potential functionality of signals A and E, QTL analyses were performed in lung tissue, bronchial epithelial brushes, and cultured BECs (Table III, Fig 5, and Table E5). 23,24,35,[39][40][41] In lung tissue samples, no eQTLs for IL33 were found (see Table E18 and Fig Table E19 in this article's Online Repository at www. jacionline.org), the tagSNP of signal A was a significant and strong eQTL for IL33, with the disease-associated allele Table II.…”
Section: Qtl/functional Investigation Of Il33 Genetic Variationmentioning
confidence: 99%
“…Single-nucleotide polymorphism rs4742170 is located in the second intron of the human IL33 gene, more than 27 kb from the distal IL33 promoter characterized in our previous work [24] and +27244 bp from the TSS. Based on the available epigenetic data [25], the 5′ part of intron 2 of the IL33 gene containing rs4742170 has a number of features typical for regulatory elements (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…For functional evaluation, we designated the region from +26297 to +28033 bp from TSS a putative enhancer and cloned it into a luciferase reporter vector (Figure 1A). We supplemented the luciferase reporter vector already containing the IL33 promoter [24] with different variants of a downstream enhancer: an irrelevant control fragment without enhancer properties; enhancer with protective (C) allele of rs4742170; and enhancer with risk (T) allele of rs4742170. The activities of these constructs were compared in NCIH-196 human lung carcinoma cell line [24].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has indicated that the A-allele of rs992969 was significantly associated with a higher mRNA level of IL-33 in bronchial brushes (P=8.3x10 -12 ) (75). In addition, a functional study has revealed that the G-allele of rs928413 was associated with higher IL-33 promoter activity compared with the A-allele in lung cancer cells, and the G-allele of rs928413 included a binding site for cyclic AMP-responsive element-binding protein 1, which is likely an activator of IL-33 transcription in the presence of this allele (76). These studies have demonstrated the potential regulatory effects of these SNPs on the transcription of IL-33.…”
Section: Discussionmentioning
confidence: 99%